Multicast-Oriented Task Offloading for Vehicle Edge Computing - Haotian Li; Xujie Li; Mingyue Zhang; Buyankhishig Ulziinyam (IEEE Access, 2020)
Vehicle edge computing (VEC) is expected to be widely used in 5G wireless network in the future owing to its low latency, high reliability, and easy deployment. Unfortunately, the computation resources of roadside units (RSUs) equipped with computing ability are limited, which makes us need to seek other computing nodes. In this article, we explore an offloading model to meet this challenge. Future vehicles equipped with computing abilities can provide VEC services in vehicular fog networks (VeFN), which greatly reduces task delay and improves the efficiency of transportation system. We consider that a package consisting of several tasks is offloaded to vehicles with different computing abilities via multicast, and these vehicles process tasks at the same time. First, we use the mathematical method to construct the system utility function, aiming to obtain low delay and low computing cost, and produce a 0-1 programming problem with inequality constraints. We then solve the slack form of the primary problem based on the interior point method. Finally, a low-complexity algorithm is proposed to optimize the task delay and cost. Numerical results show that the algorithm has fast convergence speed and superior performance.